Development Of Catalyctic Converter For Unleaded Gosaline Program In Indonesia - Oberlin Sidjabat; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1998)
Recent economic development in Indonesia, as in other ASEAN countrie, has resulted in improved prosperity as reflected by the significant increase in the numbers of motor vehicles, particulary in big cities. This growth in car population and traffic is unfortunately accompanied by increase in not only of the countryâ€™s energy consumption but also increased air pollution. Almost 70% of atmospheric pollution in big cities is reported to be contributed by motor vehicles.In view of this situation, the Government of Indonesia has launched the â€œBlue Sky programâ€ and introduced unleaded gasoline. Indonesia manufacturing industries have responded also by designing â€œnationalautomobilesâ€ to be fabricated in Indonesia, and to run with unleaded gasoline. Some of these vehicles will be equipped with catalytic converters to reduce exhaust gas emissions.In support of this program, LEMIGAS R/D Center for Oil and Gas Technology is developingits-own catalytic converters that can be fitted into these cars. The work carried out toward this end is outlined briefly in this paper